2022
DOI: 10.1002/cncy.22552
|View full text |Cite
|
Sign up to set email alerts
|

Performance of repeat cytology with reflex ThyroSeq genomic classifier for indeterminant thyroid cytology

Abstract: BACKGROUND:The American Thyroid Association recommends either repeat fine-needle aspiration biopsy (FNAB) or molecular testing (eg, ThyroSeq) of Bethesda category III (atypia of undetermined significance/follicular lesion of undetermined significance [AUS/FLUS]) nodules to provide further risk stratification. How a testing algorithm that uses ancillary molecular tests performs as a reflex test for repeat sampling of indeterminant nodules remains unclear. METHODS: Thyroid FNABs performed over a 24-month period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Proceeding with molecular testing in this context provided resolution to the indeterminate cytology of the initial FNA in approximately 60% of cases and averted the need for yet another biopsy due to the ND cytology of the repeat FNA. Prior reports of repeat FNA‐based molecular testing, including our earlier analysis of Afirma GEC cases from 2013 to 2017, have suggested that ND cytology on repeat FNA may limit the usefulness of molecular testing on the concurrent sample 11,35 . However, our current analysis of our entire Afirma GEC and GSC cohort through January 2021 supports the concept that submitting samples for molecular testing is still reasonable in this scenario, given the (1) persistently low‐to‐intermediate (9%) NIFTP and/or cancer risk, and (2) relatively high rate of satisfactory Afirma test results in this subset.…”
Section: Discussionsupporting
confidence: 57%
“…Proceeding with molecular testing in this context provided resolution to the indeterminate cytology of the initial FNA in approximately 60% of cases and averted the need for yet another biopsy due to the ND cytology of the repeat FNA. Prior reports of repeat FNA‐based molecular testing, including our earlier analysis of Afirma GEC cases from 2013 to 2017, have suggested that ND cytology on repeat FNA may limit the usefulness of molecular testing on the concurrent sample 11,35 . However, our current analysis of our entire Afirma GEC and GSC cohort through January 2021 supports the concept that submitting samples for molecular testing is still reasonable in this scenario, given the (1) persistently low‐to‐intermediate (9%) NIFTP and/or cancer risk, and (2) relatively high rate of satisfactory Afirma test results in this subset.…”
Section: Discussionsupporting
confidence: 57%
“…The structure was non-tender and was palpable only after singing. Fine needle aspiration of the lesion showed Bethesda category III cytology; molecular testing [14] found a missense c.1358T > C mutation in the TSH receptor gene [15] with variant allele frequency of 46%, negative for gene fusions or copy number variants.…”
Section: Resultsmentioning
confidence: 99%
“…With a cancer/NIFTP prevalence of 28%, the NPV was 97% [CI, 93%-99%] and PPV was 66% [CI, 56%-75%] (34) (Table 1). There have been 10 independent studies assessing the performance of TSv3 (46,47,(58)(59)(60)(61)(62)(63)(64)(65). A recent meta-analysis by Lee at al.…”
Section: The Role Of Molecular Diagnostics In Itn For Benign Vs Malig...mentioning
confidence: 99%